Anisotropic Exclusion Effect between Photocatalytic Ag/AgCl Janus Particles and Passive Beads in a Dense Colloidal Matrix - Huang, Tao; Gobeil, Sophie; Wang, Xu; Misko, Vyacheslav; Nori, Franco; De Malsche, Wim; Fassbender, Juergen; Makarov, Denys; Cuniberti, Gianaurelio (Giovanni); Baraban, Larysa (Langmuir, 2020)
Synthetic nano- and micromotors interact with each other and their surroundings in a complex manner. Here, we report on the anisotropy of active-passive particle interaction in a soft matter system containing an immobile yet photochemical Ag/AgCl-based Janus particle embedded in a dense matrix of passive beads in pure water. The asymmetry in the chemical gradient around the Janus particle, triggered upon visible light illumination, distorts the isotropy of the surrounding electric potential and results in the repulsion of adjacent passive beads to a certain distance away from the Janus particle. This exclusion effect is found to be anisotropic with larger distances to passive beads in front of the Ag/AgCl cap of the Janus particle. We provide insight into this phenomenon by performing the angular analysis of the radii of exclusion and tracking their time evolution at the level of a single bead. Our study provides a novel fundamental insight into the collective behavior of a complex mixture of active and passive particles and is relevant for various application scenarios, e.g., particle transport at micro- and nanoscale and local chemical sensing.
CRIS-Team Scopus Importer:2022-04-14